Incidence and risk factors of asbestosis among workers in industrial sector: literatur review - Sihotang, Widya Yanti; Wicaksana, Praja Dwi; Hakim, Mia Amara; Simangunsong, Pahala Maringan J.; Manalu, Putranto; Siagian, Masryna (MEDIA ILMU KESEHATAN, 2024)
Background: The industrial sector is a vulnerable place for diseases, especially lung diseases such as asbestosis. Continuous exposure of workers to asbestos has caused the incidence rate to increase over time.Objective: This review aimed to explore the factors influencing the increased incidence of asbestosis in workers in the industrial sectoreMethods: The investigation involved analyzing the results of 17 relevant previous studies using qualitative analysis procedures, variables, themes and factors were extracted from the studies.Results: The analysis revealed eight main categories: age, gender, occupation, industry type, length of exposure, education, income and smoking history. Age, gender and length of exposure were found to be the most important risk factors for asbestosis in workers at an average age of 54 years in men who had been exposed for 21 years.Conclusion: In conclusion, with the increasing incidence of asbestosis from past exposure, this study is needed as an evaluation and consideration in reducing asbestosis in workers.